Date | May 2014 | Marks available | 18 | Reference code | 14M.2.hl.TZ0.5 |
Level | HL only | Paper | 2 | Time zone | TZ0 |
Command term | Find, Hence, Show that, and Solve | Question number | 5 | Adapted from | N/A |
Question
Consider the differential equation \(\frac{{{\text{d}}y}}{{{\text{d}}x}} + y\tan x = 2{\cos ^4}x\) given that \(y = 1\) when \(x = 0\).
(a) Solve the differential equation, giving your answer in the form \(y = f(x)\).
(b) (i) By differentiating both sides of the differential equation, show that
\[\frac{{{{\text{d}}^2}y}}{{{\text{d}}{x^2}}} + y = - 10\sin x{\cos ^3}x\]
(ii) Hence find the first four terms of the Maclaurin series for \(y\).
Markscheme
(a) integrating factor \( = {e^{\int {\tan x{\text{d}}x} }}\) M1
\( = {{\text{e}}^{\ln \sec x}}\) A1
\( = \sec x\) A1
\(\sec x\frac{{{\text{d}}y}}{{{\text{d}}x}} + y\sec x\tan x = 2{\cos ^3}x\) (M1)
integrating,
\(y\sec x = 2\int {{{\cos }^3}x{\text{d}}x} \) A1
\( = 2\int {\cos x(1 - {{\sin }^2}x){\text{d}}x} \) A1
\( = 2\left( {\sin x - \frac{{{{\sin }^3}x}}{3}} \right) + C\) A1
Note: Condone the absence of \(C\).
(substituting \(x = 0,{\text{ }}y = 1\))
\(1 = C\) M1
the solution is
\(y = 2\cos x\left( {\sin x - \frac{{{{\sin }^3}x}}{3}} \right) + \cos x\) A1
[9 marks]
(b) (i) differentiating the equation,
\(\frac{{{{\text{d}}^2}y}}{{{\text{d}}{x^2}}} + y{\sec ^2}x + \tan x\frac{{{\text{d}}y}}{{{\text{d}}x}} = - 8{\cos ^3}x\sin x\) A1A1
Note: A1 for each side.
substituting for \(\frac{{{\text{d}}y}}{{{\text{d}}x}}\),
\(\frac{{{{\text{d}}^2}y}}{{{\text{d}}{x^2}}} + y{\sec ^2}x + \tan x\left( {2{{\cos }^4}x - y\tan x} \right) = - 8{\cos ^3}x\sin x\) A1
\(\frac{{{{\text{d}}^2}y}}{{{\text{d}}{x^2}}} + y({\sec ^2}x - {\tan ^2}x) = - 8{\cos ^3}x\sin x - 2\tan x{\cos ^4}x\) (or equivalent) A1
\(\frac{{{{\text{d}}^2}y}}{{{\text{d}}{x^2}}} + y = - 10\sin x{\cos ^3}x\) AG
(ii) differentiating again,
\(\frac{{{{\text{d}}^3}y}}{{{\text{d}}{x^3}}} + \frac{{{\text{d}}y}}{{{\text{d}}x}} = - 10{\cos ^4}x + {\text{term involving }} \sin x\) A1
it follows that
\(y(0) = 1,{\text{ }}y'(0) = 2\) A1
\(y''(0) = - 1,{\text{ }}y'''(0) = - 12\) A1
attempting to use \(y = y(0) + xy'(0) + \frac{{{x^2}}}{2}y''(0) + \frac{{{x^3}}}{6}y'''(0) + \ldots \) (M1)
\(y = 1 + 2x - \frac{{{x^2}}}{2} - 2{x^3}\) A1
[9 marks]